The Airline Crisis Communication: A Text Analysis of Airasia’s Press Release Related to The Plane Crash from December 28, 2014 – March 4, 2015 - Ferdinand Adi; Dorien Kartikawangi (Atma Jaya Indonesia Catholic University, Jakarta, 2016)
In the digital era, information can rapidly deploy or decrease a crisis to the whole world. Therefore, the crisis management role is to be able to communicate a crisis properly and take advantage of updated information. This research explains how an airline company managed a crisis caused by an airplane crash from the communication perspective. There’re many strategies to spread information about crisis to stakeholders, one of them is press releases. This research aimed to find out how the airline crisis communication management based on text analysis of press releases about the crash. The main theory used in this research is Aristotle’s rhetoric theory and supported by the theory of framing techniques by Fairhurst and Sarr. Through qualitative research using text analysis, the result show that press release can be a communication tool that has the power to deal with crisis when the information contains very strong key messages, delivered according to the concept of ethos, pathos, logos and framing techniques jargon and traditions.